Risk of morbidity with stomach cancer among workers employed at radiation-hazardous enterprise - G.V. Zhuntova; E.S. Grigor'eva; T.V. Azizova (Analiz Riska Zdorovʹû, 2019)
We performed retrospective research among a cohort made up of workers employed at "Mayak" Production Association (Mayak PA), a state nuclear enterprise, who had been exposed to long-term external gamma-irradiation and internal alpha-irradiation caused by plutonium-239 under inhalation introduction. Our research goal was to assess impacts exerted by occupa-tional irradiation and non-radiation factors on a risk of morbidity with stomach cancer (SC) in workers employed at Mayak PA.